Sendingteorie en sendingpraktyk in die Nederduitsch Hervormde Kerk: Verlede, hede en toekoms - Wyk, D. J. C. van (Hervormde teologiese studies, 1987)
The missionary work of the Nederduitsch Hervormde Kerk van Afrika in theory and practice: in the past, present and futureIn this article a short survey is given of the missionary work, both in theory and practice, of the Nederduitsch Hervormde Kerk during the last fifty years. There is also an indication that the Church has reached a crucial point which is going to require thorough rethinking and reconsideration of our missionary work.